A personal history of the Parks-McClellan algorithm. - McClellan, J.H.
This article describes the work that led to what is now known as the Parks-McClellan algorithm. Within the bigger picture of filter design methods, this paper recount events that had an impact on the inspiration to develop the Parks-McClellan algorithm, i.e., the Remez exchange algorithm with optimal Chebyshev approximation for FIR filter design.
Keywords: FIR filter design; Parks-McClellan algorithm; Remez exchange algorithm; Finite impulse response; Optimal chebyshev approximation; Optimal filter